Do NSAIDs affect bone healing rate, delay union, or cause non-union: an updated systematic review and meta-analysis - Chuang, Po-Yao; Yang, Tien-Yu; Tsai, Yao-Hung; Huang, Kuo-Chin (Frontiers in Endocrinology, 2024)
Introduction Nonsteroidal anti-inflammatory drugs (NSAIDs) may potentially delay or cause non-union of fractures by inhibiting prostaglandin synthesis. However, studies have shown conflicting results. This systematic review and meta-analysis aim to synthesize current evidence on the potential influence of NSAIDs on bone healing. Methods We conducted a comprehensive search of PubMed, Embase, and Cochrane CENTRAL databases for studies published up to 25 July 2023. Specific keywords included “NSAID,” “nonsteroidal anti-inflammatory drug,” “cyclooxygenase-2 inhibitor,” “bone healing,” “non-union,” “pseudoarthrosis,” “delayed union,” and “atrophic bone.” Eligible studies included prospective, retrospective, and case-controlled studies assessing the correlation between NSAID use and bone healing outcomes. The leave-one-out approach was used to test the robustness of the meta-analysis results. Results A total of 20 studies with 523,240 patients were included in the analysis. The mean patient age ranged from 6.7 to 77.0 years, with follow-up durations from 3 to 67 months. The meta-analysis revealed no significant difference in non-union or delayed union between NSAID users and non-users [pooled adjusted odds ratio (OR) = 1.11; 95% confidence interval (CI): 0.99–1.23]. Initial analysis identified a significant association between NSAID usage and an increased risk of reoperation, but this association became insignificant upon sensitivity analysis (crude OR = 1.42; 95% CI: 0.88–2.28). Discussion NSAIDs may have a minimal impact on non-union or delayed union risks. However, caution is advised due to the limited number of studies and the absence of a specific focus on NSAID types and dosages. Further research is necessary to better understand the implications of NSAID use on bone healing.